2021
DOI: 10.3390/jpm11111179
|View full text |Cite
|
Sign up to set email alerts
|

Radiomics and Artificial Intelligence in Uterine Sarcomas: A Systematic Review

Abstract: Background: Recently, artificial intelligence (AI) with computerized imaging analysis is attracting the attention of clinicians, in particular for its potential applications in improving cancer diagnosis. This review aims to investigate the contribution of radiomics and AI on the radiological preoperative assessment of patients with uterine sarcomas (USs). Methods: Our literature review involved a systematic search conducted in the last ten years about diagnosis, staging and treatments with radiomics and AI in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…In a recent systematic review carried out by our group, we discussed the heterogeneity of the various studies using artificial intelligence models to differentially diagnose leiomyosarcoma from leiomyomas [29]. Some studies showed the superiority of artificial intelligence applied to MRI in diagnostic accuracy compared to expert radiologists.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent systematic review carried out by our group, we discussed the heterogeneity of the various studies using artificial intelligence models to differentially diagnose leiomyosarcoma from leiomyomas [29]. Some studies showed the superiority of artificial intelligence applied to MRI in diagnostic accuracy compared to expert radiologists.…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of research has shown the role of radiomics in predicting patients' prognosis for various types of tumors, including gynecological cancers [25][26][27][28]. However, regarding uterine sarcomas, our recent systematic review revealed limited evidence supporting the benefit of radiomics in this pathology for pre-operative evaluation, highlighting the need for further studies [29,30].…”
Section: Introductionmentioning
confidence: 98%
“…In 2019, Nakagawa et al 59 found that a multiparametric machine learning MRI‐based method had better results in terms of diagnosis of malignancy than positron emission tomography alone and was comparable to experienced radiologists. However, according to Ravegnini et al, 60 despite growing interest for the application of AI in the differential diagnosis of uterine masses combined with MRI features, AI systems appear currently too complicated to be readily applied in daily clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the confidence and trust vested in decision-makers who employ machine learning models within specific domains are of utmost importance [20]. The enhancement of decision-making hinges on the ability to detect flaws and concealed biases within the operations of these models [21]. The utilization of artificial intelligence, particularly deep learning and machine learning models, in predicting hydrogen production brings to light the invaluable potential of these technologies.…”
Section: Introductionmentioning
confidence: 99%